Psychological attitudes of a friend in the Agananooru - A, Revathi; K, Devi Booma (International Research Journal of Tamil, 2022)
The Sangam literature lists a hundred of chronological verses in the order in which the hero presents the life of internal morals. and it also represents verses of ‘Agananooru’. The first person to appear in Sangam literature is the friend. It we look at the psychological attitude of the friend in this book, the romance and chastity of the hero and heroine to the nerd level. In this essay, she can ln seen as a literary work that puts everything on the thematic end in the hands of romance and chastity who changes or solves the veil that calms the feelings of inner demons without living for her self.